Prevalence, multiple antibiotic resistance and virulence profile of methicillin-resistant Staphylococcus aureus (MRSA) in retail poultry meat from Edo, Nigeria - Igbinosa, Etinosa O.; Beshiru, Abeni; Igbinosa, Isoken H.; Ogofure, Abraham G.; Ekundayo, Temitope C.; Okoh, Anthony I. (Frontiers in Cellular and Infection Microbiology, 2023)
Staphylococcus aureus causes staphylococcal food poisoning and several difficult-to-treat infections. The occurrence and dissemination of methicillin-resistance S. aureus (MRSA) in Nigeria is crucial and well documented in hospitals. However, findings on MRSA from meat in the country are yet to be adequately reported. The current study determined the prevalence, virulence profile and antibiogram characteristics of MRSA from a raw chicken product from retail outlets within Edo. A total of 368 poultry meat samples were assessed for MRSA using culture-based characterised using a molecular approach. Of the samples tested, 110 (29.9%) were positive for MRSA. All the isolates were positive for DNase, coagulase and beta-hemolysis production. Biofilm profile revealed 27 (24.55%) weak biofilm formers, 18 (16.36%) moderate biofilm formers, and 39 (35.45%) strong biofilm formers. The isolates harboured 2 and ≤17 virulence genes. Enterotoxin gene profiling revealed that 100 (90.9%) isolates harboured one or more genes. Resistance against the tested antibiotics followed the order: tetracycline 64(58.2%), ciprofloxacin 71(64.6%), trimethoprim 71(64.6%) and rifampin 103(93.6%). A total of 89 isolates were multidrug-resistant, while 3 isolates were resistant to all 22 antibiotics tested. The isolates harboured antimicrobial-resistant determinants such as mecA, tetK, tetL, ermA, ermC, dfrK. All the SCCmec IVa and SCCmec V positive isolates also harboured the PVL gene. We conclude that S. aureus was resistant to commonly used antibiotics, a concern to public health concerning the transmission of these pathogens after consuming contaminated chicken products. These highlight the significance of antimicrobial and enterotoxigenic monitoring of S. aureus in food chains.